Socioeconomic mobility of return migrants: evidence from Jordanian labor market surveys - Hlasny, Vladimir; Alazzawi, Shireen (Penerbit Universiti Kebangsaan Malaysia, 2022)
While the consequences of overseas migration for economic inequalities are well-documented, a relatively less researched aspect is well-being and socio-demographic status of those who chose to return to their country of origin. This paper therefore profiles returnee migrants in the Jordanian labor market as well as the causes and consequences of migration for workers’ outcomes using the 2010 and 2016 waves of the Jordanian Labor Market Panel Survey. We study changes in socioeconomic status within and across generations, linking male workers’ current outcomes to those in prior years (across different points in their careers and to their fathers’ outcomes. We assess inter-temporal social mobility as a function of their prior migration experience, socioeconomic status and demographics. In addition, we present regression evidence of how they fare in the labor market in terms of wage returns. Our data show that migration flows evolve o ver time, a nd are d riven b y s ocioeconomic a nd location-specific considerations. More specifically, migration flow from Jordan is geographically highly diffused by regional standards, as Jordanians seek high-skill jobs through formal recruiting channels. Jordanian migrants typically come from urban areas and are more educated. Return migrants are concentrated in higher earning occupations. Altogether this suggests that the labor migration process in Jordan is subject to a selection bias. However, even after controlling for background differences, we find some evidence of beneficial effect of migration for social mobility. Migrants outperform non-migrants not only in terms of current outcomes, but also in their previous occupations as well as those they held 8–10 years earlier, implying that workers’ predispositions may play a role.